Adolescent’s Reproductive Health Issues in Remote Areas with Suspected Sexual Violence: A Case Series - Gita Sirini Candijaya; JM Seno Adjie; Anna Sofyana; Desmon Andreas Lubis (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Sexual violence against adolescents is a major public health concern in Indonesia with significant medicolegal and psychosocial consequences. UNICEF estimates that more than 370 million girls in Asia have experienced sexual assault in childhood, while Indonesia’s 2021 National Survey reported a 6.9% lifetime prevalence among youth. Adolescents are particularly vulnerable due to stigma and limited access to adolescent-friendly services. Clinical descriptions of medicolegal genital findings in Indonesian adolescents remain limited.Case Presentation: This case series describes three female adolescents aged 16–18 years who underwent medicolegal genital examination following alleged sexual assault. Two patients had fresh hymenal lacerations consistent with acute penetrative trauma, while one had healed hymenal lacerations. All presented with emotional distress and received clinical assessment, reproductive health counseling, and recommendations for psychological support, sexually transmitted infection evaluation, and follow-up care. Examinations were conducted according to national forensic protocols.Conclusion: Normal or healed genital findings do not exclude sexual violence. Obstetricians and gynecologists play an important role in trauma-informed care. Multisectoral collaboration is needed to ensure comprehensive management and long-term support for adolescent survivors.Temuan Genital Medikolegal pada Remaja dengan Dugaan Kekerasan Seksual di Daerah Terpencil: Seri KasusAbstrakPendahuluan: Kekerasan seksual pada remaja merupakan masalah kesehatan masyarakat di Indonesia dengan konsekuensi medikolegal dan psikososial yang bermakna. UNICEF memperkirakan lebih dari 370 juta anak perempuan di Asia pernah mengalami kekerasan seksual pada masa kanak-kanak, sedangkan Survei Nasional Indonesia tahun 2021 melaporkan prevalensi seumur hidup sebesar 6,9% pada kelompok usia muda. Remaja rentan akibat stigma dan keterbatasan akses terhadap layanan yang ramah remaja. Deskripsi temuan genital medikolegal pada remaja Indonesia masih terbatas.Laporan Kasus: Seri kasus ini melaporkan tiga remaja perempuan usia 16–18 tahun yang menjalani pemeriksaan genital medikolegal setelah dugaan kekerasan seksual. Dua pasien menunjukkan laserasi himen baru yang konsisten dengan trauma penetratif akut, sedangkan satu pasien memiliki laserasi himen yang telah sembuh. Seluruh pasien mengalami distres emosional dan mendapatkan asesmen klinis, konseling kesehatan reproduksi, serta anjuran dukungan psikologis, evaluasi infeksi menular seksual, dan tindak lanjut.Kesimpulan: Temuan genital yang normal atau telah sembuh tidak menyingkirkan kemungkinan kekerasan seksual. Dokter spesialis obstetri dan ginekologi berperan penting dalam pelayanan berbasis trauma, dengan kolaborasi multisektoral untuk menjamin penanganan komprehensif dan dukungan jangka panjang bagi penyintas remaja.